2013
DOI: 10.7150/ijbs.5453
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cytotoxicity for Colon 26 Cells Using Doxorubicin-Loaded Sorbitan Monooleate (Span 80) Vesicles

Abstract: Span 80 (sorbitan monooleate) vesicles behaved differently from conventional phospholipid vesicles (liposomes) because the former had a more fluid interface. After doxorubicin hydrochloride (DOX) was encapsulated into the Span 80 vesicle (loading efficiency: 63 %), DOX-loaded Span 80 vesicles (DVs) were thereafter added to Colon 26 cells. It was suggested, from the flow cytometric analysis and confocal laser microscopic observation, that DVs directly deliver DOX into the cytoplasm of Colon 26 cells. DVs showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Our findings suggest that the higher tumor selectivity of Span 80 vesicles may be associated with their pegylation as well as high fluidity and flexibility, which result in higher vascular permeability and tendency to fuse with the instable cell membrane of the tumors ( 27 ). Indeed, a cell fusion model of Span 80 vesicles has been recently reported ( 11 ).…”
Section: Discussionmentioning
confidence: 87%
“…Our findings suggest that the higher tumor selectivity of Span 80 vesicles may be associated with their pegylation as well as high fluidity and flexibility, which result in higher vascular permeability and tendency to fuse with the instable cell membrane of the tumors ( 27 ). Indeed, a cell fusion model of Span 80 vesicles has been recently reported ( 11 ).…”
Section: Discussionmentioning
confidence: 87%
“…The increased lung uptake thus can be attained. The addition of phospholipids in nanosystems elevates the interface rigidity and biocompatibility [11,12]. It is hypothesized that incorporation of PC would target the niosomes to the lungs and minimize the propensity for liver and spleen uptake, making the nanovesicles more attractive for drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study indicated that higher vascular permeability and inclination to fuse with the instable cell membrane of the tumors based on high fluidity and flexibility as well as pegylation could result in the higher tumor selectivity of Span 80 vesicles [52]. Recently, a cell fusion model using Span 80 vesicles has been reported [27].…”
Section: Discussionmentioning
confidence: 66%
“…The next-generation liposomes with membrane-bound-targeting molecules have also been under development. An anticarcinoma application of Span 80 vesicles containing doxorubicin with or without membrane-bound-targeting molecule was recently reported [52]. As described above, Span 80 has favorable physicochemical properties; moreover, it also confirmed risk-free information because it has been already used as a stabilizer for injected drugs.…”
Section: Discussionmentioning
confidence: 72%